Recent advances in intrusion detection 14th international symposium, RAID 2011, Menlo Park, CA, USA, September 20-21, 2011 : proceedings - RAID (Symposium) 2011 Menlo Park, Calif.); Sommer, Robin; Balzarotti, Davide; Maier, Gregor 1979-.; SpringerLink (Online service). (Berlin New York Springer, 2011)
This book constitutes the proceedings of the 14th International Symposium on Recent Advances in Intrusion Detection, RAID 2011, held in Menlo Park, CA, USA in September 2011. The 20 papers presented were carefully reviewed and selected from 87 submissions. The papers are organized in topical sections on application security; malware; anomaly detection; Web security and social networks; and sandboxing and embedded environments.
Electronic reproduction.
Keywords: Intrusion detection systems (Computer security) -- Congresses; Electronic books